Abruptly Dogen - Dōgen, 1200-1253 (punctum books, 2022)
"In the thirteenth century Dogen brought Zen to Japan. His tradition flourishes there still today and now has taken root across the world. Abruptly Dogen presents some of his pith writings - startling, shifting, funny, spilling out in every direction. They come from all seventy-five chapters of his masterwork, the Eye of Real Dharma (Shōbōgenzō), and roam through mountains, magic, everyday life, meditation, the nature of mind, and how the Buddha is always speaking from inside our heads"--Page 4 of cover.